TINJAUAN YURIDIS TERHADAP ITSBAT NIKAH ADANYA PERKAWINAN DALAM PENYELESAIAN PERCERAIAN DI PENGADILAN AGAMA PADANG - Adriani Adnani (Ensiklopedia of Journal, 2023)
Abstract: Considering that the application for cumulation of itsbat nikah is filed contentiously, so the trial process is not the same as itsbat nikah for validating marriages. These differences, for example, are separated into separate requests and separate decisions, because it will give birth to a legal interpretation of the cumulation of itsbat marriage decisions which contain legalization of marriage and divorce.Keywords: itsbat of marriage, legalization of marriage and divorce.